Walkable Neighborhoods: The Link between Public Health, Urban Design, and Transportation - Oka, Koichiro (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It is now widely recognized that individual-based motivational interventions alone are not sufficient to address the global pandemic of physical inactivity (lack of exercise and too much sitting time). There has been a growing interest in the effect the physically built environment can have on people's active behaviors. The fundamental assumption is that surrounding physical environments can support active behaviors among a large number of people with long-term effects. This topic has received much attention over the last decade, mainly in the three fields of urban design, public health, and transportation. This Special Issue aims to provide multidisciplinary and evidence-based state-of-the-art research on how the locations where people live impact their active behaviors and health outcomes.